GROWTH COEFFICIENT AND FECUNDITY OF CHITALA CHITALA (OSTEOGLOSSIFORMES: NOTOPTERIDAE) FROM THE RIVER RAVI, PAKISTAN - A. Hussain; H. A. Shakir; S. Ali; J. I. Qazi (Journal of Animal and Plant Sciences, 2015)
Chitala chitala contributes much to the food as well as aquarium ornament of South Asian countries. The species deserves high conservatory impacts due to rapid decline of its natural habitats at alarming levels in addition to facing heavy pollution and fishing pressures in the last few decades. In the present study, 27 female specimens ranging from 50.6 to 68.4cm (60.6±5.29cm) total length and 937 to 2208g (1629±364g) wet body weight were collected from the village Nano Dogar, river Ravi, Pakistan. The relation between total length and weight of C. chitala was described by Log W= -1.4525 + 2.6133Log L indicating negative allometric growth. Mean absolute fecundity was calculated as 13431±2144 in sampled fish. To the best of authors’ knowledge, length-weight relationship and fecundity of this species from the river Ravi, Pakistan is being reported for the first time. This study will be very helpful in conservation and management of the feather back chital.
Keywords: Fecundity; gonado-somatic index; length-weight relationship; endangered species; river Ravi